A teoria de tudo nada: uma hipótese acerca dos “movimentos” do pensar - Scheffer, Ana Paula (2023)
Depending on your associations, perhaps when reading the title you were reminded of the idea of a theory that aims to explain the universe. This is because the word everything is commonly associated the idea of ​​cosmos, in addition to “The Theory of Everything” being the name of a film based on the life of physicist known for theories about the universe, Stephen Hawking. But, make no mistake, the word everything is properly taxed for some good reasons. The first of them aims to recognize my limitation or even inability to understand everything; the second, aims to question what would it all be? And the third, intends to guide that, perhaps, the response of second question is limited to our language system. Here we come to the subtitle: “a hypothesis about the “movements” of thinking” and the summary itself: a theory of language that aims to investigate what movements accompany thought and how they participate in our way of understanding and relating to the world. The fun here was discovering that, far beyond images and voices, the way we think can reveal important understandings about ideas such as: space, time, logic, numbers, words, meaning and even the truth – and the appropriate lies told about it. Otherwise, the The word “all” comes from Latin and means whole or that is not divided into parts, and therefore, even though there is a tendency to place this work in a little box called “philosophy”, we can say that it is an effort to transcend limits and unite philosophy, physics, science, spirituality and everyday life. The fundamental ingredients and fresh from our nothing theory!